Untargeted metabolomic analyses reveal the diversity and plasticity of the specialized metabolome in seeds of different Camelina sativa genotypes. (6th February 2022) - Boutet, Stéphanie; Barreda, Léa; Perreau, François; Totozafy, Jean‐Chrisologue; Mauve, Caroline; Gakière, Bertrand; Delannoy, Etienne; Martin‐Magniette, Marie‐Laure; Monti, Andrea; Lepiniec, Loïc; Zanetti, Federica; Corso, Massimiliano
Significance Statement: Seeds produce a myriad of specialized metabolites (SMs) with an essential role in the interaction of plants with the environment. We characterized SM landscapes, primary metabolites and lipid composition in the seeds of camelina genotypes grown in the open field in five consecutive growing seasons. Our results showed the predominant effect of the environment on the regulation of the seed SM, with a potential impact on seed quality of camelina that may also occur in other oilseed crops. SUMMARY: Despite the essential role of specialized metabolites (SMs) in the interaction of plants with the environment, studying the ability of crop seeds to produce these protective compounds has been neglected. Furthermore, seeds produce a myriad of SMs, providing an interesting model to investigate their diversity and plasticity. Camelina sativa gained a lot of interest in the past few years as a rustic oilseed crop. A characterization of seed SM landscapes in six camelina genotypes grown in the field and harvested during five growing seasons has been undertaken in this work. This allowed a comprehensive annotation of seed SMs combining analyses that cluster SMs based on their chemical structures and co‐accumulation patterns. These data showed broad effects of the environment on the stimulation of the seed SM. Among well‐annotated compounds, flavonols were identified as the metabolic class characterized by high plasticity, revealing significant variable accumulation according to the year and/or the genotype. Lastly, a deeper characterization of primary metabolites and lipids in two selected genotypes has been performed. We showed that, in addition to flavonols, alkaloids and glucosinolates displayed a higher phenotypic plasticity with respect to most of the primary metabolites, including some sugars and major storage compounds such as fatty acids, proteins and most lipid classes (e.g. diacylglycerols, triacylglycerols), but similar plasticity compared with free amino acids and carboxylic acids. This work highlighted major and unexplored effects of the environment on the seed SM, demonstrating that seeds exhibit a dynamic and plastic metabolism, with an impact on seed quality.